All fun and games [videorecording (DVD)] - Brainde, J. J.; Costa, Ari; Celeboglu, Eren; Dyer, Natalia, 1997-; Butterfield, Asa, 1997-; Ainsworth, Benjamin Evan (Vertical, 2023)
The Russo Brothers' AGBO presents a terrifying tale about a group of Salem teens who discover a cursed knife that unleashes a demon that forces them to play gruesome, deadly versions of childhood games where there can be no winners, only survivors.